Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Minat Beli Ulang di Obihiro Nikudon Blok M, Jakarta Selatan - Gavrila, Arya; Gantina, Devita; Swantari, Anita (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2105, 2026)
This study aims to examine the influence of product quality and service quality on customers' repurchase intention at Obihiro Nikudon Blok M, South Jakarta. A quantitative approach employing descriptive and verificative methods was adopted. The study population consisted of customers of Obihiro Nikudon Blok M, and the sample was selected using purposive sampling based on respondents who had previously purchased products from the restaurant. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression, supported by validity, reliability, partial, and simultaneous significance tests. The findings indicate that all research instruments met the required validity and reliability criteria. Furthermore, the results reveal that both product quality and service quality have a positive and significant effect on customers' repurchase intention, both individually and simultaneously. Among the two independent variables, service quality exerts a relatively stronger influence on repurchase intention than product quality. The study concludes that consistently improving product quality and service quality is essential for enhancing customers' repurchase intention and sustaining customer loyalty in the Japanese restaurant industry. Keywords: product quality, service quality, repurchase intention